(untitled) (Phoenix: International Multidisciplinary Research Journal ( Peer reviewed High Impact Journal ), 2026)
The Mahatma Gandhi National Rural Employment Guarantee Act (MNREGA) has emerged as one of India’s most significant rights-based welfare initiatives aimed at enhancing rural livelihood security. Introduced in 2005, the programme guarantees 100 days of wage employment to every rural household willing to undertake unskilled manual labour. While its economic implications have been widely studied, the sociological dimensions—changes in labour relations, social inclusion, migration patterns, gender participation, and empowerment deserve deeper, systematic analysis.